Transformation of Historical Media of Rokan Palace Through Motion Graphic Media as a Visual Education Approach - Ramadhaniel, Muhammad Fazlan Nur; Afdhal, Vernanda Em (Gorga : Jurnal Seni Rupa, 2025)
Local history and culture significantly contribute to the formation of collective identity and serve as a means of education to preserve ancestral heritage. Rokan Palace, embodying Malay culture in Rokan Hulu Regency, holds immense historical and cultural significance. However, the younger generation exhibits a diminished interest and lack of concern for preserving these historical and cultural values. This challenge necessitates a creative approach. This study employs motion graphic media as an innovative medium to present history in an interactive, engaging, and relevant manner to the digital era. The design methodology employed adheres to the historical approach, encompassing four primary stages: heuristics, external and internal criticism, interpretation, and historiography. The outcomes of this study present motion graphic media as a visual education approach for conveying the history of Rokan Palace. This design has undergone feedback from respondents, demonstrating its effectiveness in conveying history to the younger generation and contributing to the preservation of cultural heritage.